The relationship between temperament and fearfulness in adult dental phobic patients - JESPER LUNDGREN, MAGNUS L. ELFSTRÖM, & ULF BERGGREN (IAPD and Blackwell, 2007)
Dental fear (DF) may cause frequent and serious problems for both the dentist and patient, and it often gives rise to a number of deleterious effects.